Antibody response to the 45 kDa Candida albicans antigen in an animal model and potential role of the antigen in adherence - Bujdáková, Helena; Paulovičová, Ema; Borecká-Melkusová, Silvia; Gašperík, Juraj; Kucharíková, Soňa; Kolecka, Anna; Lell, Claudia; Jensen, Dorthe B; Würzner, Reinhard; Chorvát, Dušan; Pichová, Iva (Journal of medical microbiology, 2008)
The Candida antigen CR3-RP (complement receptor 3-related protein) is supposed to be a 'mimicry' protein because of its ability to bind antibody directed against the alpha subunit of the mammalian CR3 (CD11b/CD18). This study aimed to (i) investigate the specific humoral isotypic response to immunization with CR3-RP in vivo in a rabbit animal model, and (ii) determine the role of CR3-RP in the adherence of Candida albicans in vitro using the model systems of buccal epithelial cells (BECs) and biofilm formation. The synthetic C. albicans peptide DINGGGATLPQ corresponding to 11 amino-acids of the CR3-RP sequence DINGGGATLPQALXQITGVIT, determined by N-terminal sequencing, was used for immunization of rabbits to obtain polyclonal anti-CR3-PR serum and for subsequent characterization of the humoral isotypic response of rabbits. A significant increase of IgG, IgA and IgM anti-CR3-RP specific antibodies was observed after the third (P<0.01) and the fourth (P<0.001) immunization doses. The elevation of IgA levels suggested peptide immunomodulation of the IgA1 subclass, presumably in coincidence with Candida epithelial adherence. Blocking CR3-RP with polyclonal anti-CR3-RP serum reduced the ability of Candida to adhere to BECs, in comparison with the control, by up to 35 % (P<0.001), and reduced biofilm formation by 28 % (P<0.001), including changes in biofilm thickness and integrity detected by confocal laser scanning microscopy. These properties of CR3-RP suggest that it has potential for future vaccine development.
Keywords: protilátky fungální; imunizace; Antibodies, Fungal; Humans; antigeny fungální; Antigens, Fungal; fungální proteiny; Molecular Sequence Data; molekulární sekvence - údaje; sekvence aminokyselin; Biofilms; Receptors, Complement; epitelové buňky; Cell Adhesion; lidé; zvířata; Amino Acid Sequence; ústní sliznice; Epithelial Cells; biofilmy; receptory komplementu; králíci; Mouth Mucosa; Candida albicans; Animals; buněčná adheze; Fungal Proteins; Disease Models, Animal; Rabbits; Immunization; modely nemocí na zvířatech